Pengaruh Gaya Kepemimpinan Pemilik Usaha Terhadap Kinerja Karyawan Pada UMKM Café Allya - Cindy Rahmadani; Zara Hayati; Inka Bella Novratiwi Saputri; Vivi Nila Sari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The purpose of this research is to analyze and find solutions to the problems occurring between employees and the business owner at Café Allya. This business wass established with the goal of generating profit. Ist strategic location near a university makes it easier for the business does not employ many employees. In this study, we used interviews as one of the data collection techniques. This method allows researchers and respondents to interact directly, making it easier for the researchers to analyze the problems. Based on these interviews, it can be concluded that the causes of the problems are a lack of work motivation and an ineffective leadership style, which affect employee performance. Additionally, emotions and mood also influence employee job satisfaction.